Contribution of PERSSILAA project to evaluate the nutritional status among elderly people - Albuquerque, T.G. (2015)
PERsonalised ICT Supported Service for Independent Living and Active Ageing (PERSSILAA) is an European project (FP7-610359) that aims to develop and validate a new service model for older people, to screen for and prevent frailty. This multimodal service model, focusing on nutrition, physical and cognitive function is supported by an interoperable ICT service infrastructure. PERSSILAA project is structured in six workpackages. The objective of WP3 is the development and validation of the various service modules focused on nutrition, physical and cognitive functioning. The task screening modules aims to develop an easy to use multidimensional screening tool integrating different domains important for frailty, specifically cognitive, physical and nutritional status to generate a quick, reliable and integrated assessment of a person’s health status. For nutrition, the Mini Nutritional Assessment (MNA®) will be used. Under WP3, one of the tasks is Nutrition, which focuses on the development of training services to promote healthy behaviour in terms of healthy nutrition, and can be offered via different service configurations, such as a health literacy program, health promoting self management tools or as (in)formal care supported service. An interactive website that offers various modules, 15 in total, will be developed. Examples are: 1) clinical nutrition and 2) nutritional labelling. In the 1st module the objective is: with the intervention of a nutritionist, with experience in clinical practice and a patient, we will simulate what happens in a real nutritional intervention. Therefore during this intervention we will show how to assess the following topics: family history, lifestyle habits, nutritional assessment, nutritional status (including anthropometric data), and dietary plan. The 2nd module, regarding nutritional labelling, aims to provide information to consumers about the characteristics of packaged food products so that after reading it, they make appropriate food choices for each case as well as a proper preparation, consumption, storage and conservation. For this purpose, we intend to help the general public to better interpret food labels, giving them comprehensive information and education on the current legislation (Regulation EU n.º 1169/2011). With these modules, we intend that in the near future elderly people can learn how to make healthier choices and improve food habits, providing them tools to allow people to easily evaluate themselves.